Implementation of an automated transition readiness assessment in a pediatric rheumatology clinic - Argraves, Melissa; Murray, Elizabeth; Taxter, Alysha; Wise, Kelly; Jensen, Paul T.; Goldstein-Leever, Alana; Thomas, Bethanne; Scott, Alexa; Gallup, James; Leone, Ashlee; Ardoin, Stacy P.; Sivaraman, Vidya (Frontiers in Pediatrics, 2024)
Background: Failure of successful transition to adult care for adolescents and young adults with chronic rheumatic diseases negatively impacts their health and wellbeing. Transition of care is a vital and complex process within pediatric rheumatology that can be difficult to execute. Use of quality improvement (QI) and clinical informatics (CI) can help implement transition programs. Local Problem: Despite efforts to improve transition of care within our pediatric rheumatology clinic, it has been difficult to implement and sustain good transition practices including assessment of transition readiness. Using QI methodology and CI, this study aimed to improve transition readiness assessment from 12 to 30% and sustain for one year by surveying transitioning patients yearly. Methods: A transition-focused QI team utilized methods endorsed by the Institute for Healthcare Improvement and leveraged CI to improve survey completion. Control charts of survey completion rates were tracked monthly. Descriptive statistics were used to analyze survey responses. Interventions: Interventions focused on automation of patient surveys at regularly scheduled clinic visits. Results: 1265 questionnaires were administered to 1158 distinct patients. Survey completion rose from a baseline of 12% to greater than 90% and was sustained over 18 months. Identified educational needs included health insurance, scheduling appointments, obtaining care outside of rheumatology clinic business hours, Electronic Health Record messaging, and refilling medications. Conclusions: By leveraging CI and QI methodology, we were able to assess transition readiness in more than 90% of our patients and identify gaps in self-management. Process automation can create sustainable transition practices.